Penerapan Metode Ta’wīd Symposium Pembelajaran Bahasa Arab di Pondok Pesantren - Alif Pratama, Moch Reza; Anwar, Najih (Study Program of Arabic Language Teaching, 2025)
This study aims to analyze the effectiveness and form of application of the ta’wīd method. The material's content, stages, and benefits of using the method will be described systematically. This study was conducted using a qualitative method with a case study approach. The data in this study were taken from the interview process and direct observation of informants. The data obtained include the teaching materials used, the stages of using the ta’wīd method in the symposium, the learning styles obtained by the students, and the cycles that occur. Data sources are taken from primary and secondary data. Primary data is obtained through interviews with students, teachers, and curriculum leaders, as well as the results of observations during the learning process. At the same time, secondary data is taken from previous studies accessed through journals and books on the website. Data collection techniques are carried out through interviews, direct observation, and documentation in the form of photos of teaching materials. Data analysis techniques in this study are carried out through data collection, data reduction, data presentation, and conclusion. Based on the research results, students have a large new vocabulary in Arabic and can pronounce it by heart, even some students have even started to get used to using Arabic in everyday life. The target of implementing this learning is that all students become more confident in having dialogues using Arabic.